Unsolved - Patterson, James 1947-; Ellis, David 1967; Collins, Kevin T.; Pressley, Brittany; Patterson, James, 1947- (New York, NY : Hachette Audio, 2019)
"Indomitable FBI researcher Emmy Dockery ("Invisible") returns with a shocking new case. Across the country, victims appear to have died by accident, and seemingly have nothing in common. But this many deaths can't be coincidence. And the killer is somehow one step ahead of every move Dockery makes."--Provided by publisher.
Keywords: Government investigators -- Fiction; Murder -- Fiction -- Investigation; Serial murders -- Fiction; Government investigators; Murder -- Investigation; Serial murders; Audiobooks; Fiction; Novels; Thrillers (Fiction); Mystery fiction; Thrillers (Fiction); Detective and mystery fiction; Novels; Audiobooks